Crecimiento, producción y composición química de la berenjena ‘ciça’ bajo fertirrigación potásica - Almeida Monaco, Kamila De [UNESP]; Baptista Borelli, Aline; Biscaro, Guilherme Augusto; Motomiya, Anamari Viegas De Araujo; Zomerfeld, Patricia Dos Santos (My University, 2016)
The objective of this study was to evaluate the effect of potassium applied through fertigation in coverage of the development, production and chemical composition of eggplant ‘Ciça’ in an Oxisol. The treatments consisted of five rates of K2O (0, 36, 72, 108 and 144 kg ha-1 supplied by fertigation) and is used as source of potassium, in six installments topdressing applications. The irrigation system was of the type localized and drip irrigation was conducted via tank evaporimeter Class A. The harvest began 62 Days After Transplanting (DAT) extending by five months, and the characteristics were evaluated: plant height, leaf number, average weight, average length and average fruit diameter, fruit number per plant, production per plant, yield and fruit classification according to their size. At 85 DAT was performed to collect fruit for characterization as to the percentage of lipids, protein and fiber. Spite of potassium fertigation provide coverage for a reduction in the production and yield, the concentrations 36 kg ha-1 and 72 kg ha-1 of K2O applied through fertigation, increased features physicochemical evaluations.
Crescimento, produção e composição química de berinjela ‘ciça’ sob fertirrigação potássica
Growth, production and chemical composition of eggplant ‘ciça’ under potassium fertigation
Keywords: Fruit quality; Nutrition; Solanum melongena l